The Degree of Implementation of The Strategy of Mental Maps of The Teachers of English Language in The Province of Damascus - Kishik, Mona; Ziab , Rasha (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The aim of the research has aimed to identify the extent of the implementation of the strategy of mental maps in English teachers in Damascus governorate. In addition, it has aimed to identify the differences between the average grades of teachers in the application of the strategy of mental maps according to the variables (type of education and qualification). The survey has been applied on the second cycle of Basic Education in ( 2016-2017) . As for the study sample , it included (62) teachers , they have been chosen randomly .The researcher has followed the discriptive analytical approach in her survey and she has used the questionnaire as a means to achieve the objectives of the research after it was tested for its vadility and reliability. The questinnaire of mental maps has been applied to them , which is prepared by the researcher . -The research concluded the following results: - Implementation of the strategy of mental maps of English teachers in the schools of the second cycle of basic education was a medium degree. - There are statistically significant differences between the average grade of English teachers in the second cycle schools of the basic education level on the extent to which mental maps are applied according to the type of education variable in favor of special education. - There are statistically significant differences between the average grade of English teachers in the second cycle schools of the basic education level on the extent of applying mental maps strategy according to the variable of scientific qualification for teachers with the highest qualifications.